RESILIENCE & REINVENTION: A PATH FOR CHANGE IN MANAGEMENT, IT, MEDIA AND LAW - Ahuja, Nitya (Trinity Law Review, 2023)
“A lawyer is able to contribute to national development and social change in a very constructive manner with legal education.At this time of globalization, information technology is a blessing, it is a multi- dimensional field which is bridged with fields like education, payments, coding, security works, etc. education is not just linked to the field of law alone, it touches the arena of social, political and economic aspects of the society as well. Education acts a powerful weapon which plays a vital role in changing the aspects that rule the world. Better the education, better the way the world runs. A layman definition to information technology can be termed as ‘the study or the use of electronical equipment, especially computers with an intent to collection, store and share information.’ Information technology is a boon to the new growing world wherein, not only there is development in the technology but there is also an advancement in the society. Education and technology go hand in hand, it is used by teachers, students, scholars, practitioners, analysists and all the people covered under the education strata. The importance of information technology in legal education was felt during the time of COVID- 19 which made work from home a habit. Although it was a compulsion but later it turned out tot be a part of the comfort zone of the people. Students were taught using various online sources and most importantly the court started to run via online mode, which help save a lot of money and energy of the lawyers, judges as well as the parties. The various aspects relating to the advancement of legal education due to the presence of information technology has been mentioned further in the paper.
Keywords: Development; Globalization; Information; Information Technology; Law; Legal Education; Legal Fraternity; Profession